PERFORMA REPRODUKSI INDUK TERNAK BABI DI KECAMATAN NUSANIWE KOTA AMBON - Diana M. Pelmelay; Demianus Ferdinand Souhoka; Jusak Labetubun (MARSEGU : Jurnal Sains dan Teknologi, 2024)
This study aims to determine the reproductive performance of pig farmers in Nusaniwe District, Ambon City. The research was carried out in Nusaniwe District, Ambon City, for 1 month using a survey method with interview techniques. The variables observed in the study were livestock ownership, livestock population, and reproductive performance of the parent including the age of the first mating, the age of the first calving, the length of pregnancy, litter size, calving distance, mortality and signs of fertility. The results showed that the average ownership of pigs based on the age phase of starter, grower, finisher and parent was 9.08 heads (0.9 ST), 6.32 heads (1.26 ST), 1.33 heads (0.53 ST) and 3.33 heads (1.33 ST) respectively. The population structure based on sex is dominated by female cattle 60.75%, and male cattle only 39.24%, while based on the level the respective ages of children were 45.15%, young 23.40%, and adults 23.40%. The reproductive performance of sows showed that the average age of first mating was 9.84±1.89 months, the first calving age was 13.98±1.83 months, the gestation duration was 11628±2.93 days, the litter size was 5.56±2.47 heads, the calving distance was 8.95±1.29 months, and the mortality was 0.33%. The signs of birahi that farmers understand are restless and silent when riding 66.2%, not knowing 33.8%. It was concluded that the reproductive performance of sows in Nusaniwe District was good.